Surface integrity and removal rate of silicon sputtered with focused ion beam - Hung, NguyenPhu; Ali, Mohammad Yeakub; Fu, Yongqi; Ong, NanShing; Tay, MengLeong (Taylor and Francis Inc., 2001)
This paper investigates the micromachinability of (100) silicon by focused gallium ion beam sputtering at normal incident angle. Effect of the beam parameters (dose, aperture and accelerating voltage) and the beam scanning parameters (pixel spacing, dwell time, retracing time and scanning type) on the surface integrity and material removal rate were studied. Statistical models derived from factorial experiments were used to predict the sputtered depths and material removal rates of silicon. The sputtering depth increased with higher accelerating voltage, more ion dose, shorter pixel spacing, and longer dwell time. Similar trends were found for predicting the material removal rate. A surface roughness in the range 2-5 nm was achieved, and was found to be linearly dependent on the pixel spacing.